(-3x-4)-(-2x-1)=6

Simple and best practice solution for (-3x-4)-(-2x-1)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-3x-4)-(-2x-1)=6 equation:


Simplifying
(-3x + -4) + -1(-2x + -1) = 6

Reorder the terms:
(-4 + -3x) + -1(-2x + -1) = 6

Remove parenthesis around (-4 + -3x)
-4 + -3x + -1(-2x + -1) = 6

Reorder the terms:
-4 + -3x + -1(-1 + -2x) = 6
-4 + -3x + (-1 * -1 + -2x * -1) = 6
-4 + -3x + (1 + 2x) = 6

Reorder the terms:
-4 + 1 + -3x + 2x = 6

Combine like terms: -4 + 1 = -3
-3 + -3x + 2x = 6

Combine like terms: -3x + 2x = -1x
-3 + -1x = 6

Solving
-3 + -1x = 6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + -1x = 6 + 3

Combine like terms: -3 + 3 = 0
0 + -1x = 6 + 3
-1x = 6 + 3

Combine like terms: 6 + 3 = 9
-1x = 9

Divide each side by '-1'.
x = -9

Simplifying
x = -9

See similar equations:

| 4(3x-5)+6=x | | 5g+14g+3= | | 4m-2=5m+7 | | 30x^2-85x+60=0 | | -2(5+6k)+16=-90 | | A^3-7a^2+6a-10= | | 4a+11-1a=2 | | 6x-4+2x-2=90 | | 42=7f | | 1300.4624=2*3.14*38.44+2*3.14*6.2*h | | -3(-10+6x)=30 | | x+13+2x+17=180 | | 1300.46=2*3.14*38.44+2*3.14*6.2h | | 80=-16t^2+35t+12 | | 6x=40+x | | 1300.46=2*3.14*38.44+2*3.14*6.2 | | -6(3+2x)=-8-2x | | y=5x-3+5x+2 | | 5(7+2x)=x-13+5x | | 0.4(x+70)+0.2x=6 | | D^2-36d+324=0 | | s=10p | | 8(7-m)=-24 | | 1300.46=2*3.14r^2+2*3.14*6.2 | | y=100+x+(7-x) | | y(15x-18)= | | 4x+7+3x-17=180 | | X=-16x^2+38 | | 2x-x^2=.91 | | 3b^2-4b-4= | | z^2+11z=-24 | | -5+2(1)=-4 |

Equations solver categories